Combinatorial Formulae for Nested Bethe Vectors - Tarasov, V.; Varchenko, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
We give combinatorial formulae for vector-valued weight functions (off-shell nested Bethe vectors) for tensor products of irreducible evaluation modules over the Yangian Y(glN) and the quantum affine algebra Uq(glN˜).